2014
DOI: 10.5935/1415-2762.20140034
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of the nurses' work process in the family health strategy

Abstract: Pesquisa descritiva de caráter qualitativo que utilizou como técnica de coleta de dados a observação sistemática não participante. O estudo teve como objetivo caracterizar as atividades laborais desenvolvidas pelos enfermeiros que atuam na Estratégia Saúde da Família (ESF) em uma unidade de saúde em um município do Sul do Brasil, de acordo com as cinco dimensões do processo de trabalho em enfermagem: participar politicamente, assistir, administrar, pesquisar e ensinar. Foram observadas e registradas as ativida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 6 publications
1
19
0
5
Order By: Relevance
“…In this perspective, there is a study that characterized the activities developed by the nurses of a FHU in a municipality of the South of Brazil and found that the inputting of the information system was the activity which had highest occurrence in the FHU, thus, they emphasize the importance of this activity in the work process of a health service, because it is a tool that provides support for decision making, with emphasis on the process of care, management and evaluation/monitoring, not only in the health unit, but at all levels of care that makes up the Unified Health System (UHS). 1 It is also necessary to guarantee the quality of the information so that the interpretation of the data is adequate, aiming at the quality of health care 18 , which was taken into account by the FHU team when identifying the inadequacy of the data and proposing its monitoring.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this perspective, there is a study that characterized the activities developed by the nurses of a FHU in a municipality of the South of Brazil and found that the inputting of the information system was the activity which had highest occurrence in the FHU, thus, they emphasize the importance of this activity in the work process of a health service, because it is a tool that provides support for decision making, with emphasis on the process of care, management and evaluation/monitoring, not only in the health unit, but at all levels of care that makes up the Unified Health System (UHS). 1 It is also necessary to guarantee the quality of the information so that the interpretation of the data is adequate, aiming at the quality of health care 18 , which was taken into account by the FHU team when identifying the inadequacy of the data and proposing its monitoring.…”
Section: Discussionmentioning
confidence: 99%
“…Nursing work encompasses five dimensions: assisting; managing; researching; political participation; and teaching; which can be performed concomitantly in a complementary and interdependent way, so that each dimension presents its own elements (object, means/instruments and activity). 1 As coordinator of the caring process, it is indispensable for the nurse to apply tools in the dynamics of care and service so that an effective and efficient practice can take place in any of the dimensions of their work, for example, to use management tools that can achieve the proposed objectives. 2 One of these tools is the dimensioning of personnel in nursing, fundamental for the adequate forecasting of professionals, quantitatively and qualitatively, aiming to attend to the needs of the assisted population in consonance with the particularity of the different health services scenarios, in order to provide quality to assistance, aiming the safety of users and workers.…”
Section: Introductionmentioning
confidence: 99%
“…Para classificação destas atribuições, consideraram-se as seguintes dimensões do trabalho do enfermeiro: administrar, assistir, ensinar, pesquisar e participar politicamente (46)(47) , utilizadas na Estratégia Saúde da Família, porta de entrada da rede de atenção à saúde (5,8,11,40) . No entanto, considerando que as atribuições obtidas nos documentos descrevem a prática no serviço de saúde, as dimensões possíveis nesta pesquisa são administrar/gerenciar e assistir/ cuidar, que têm sido as únicas duas dimensões referidas em pesquisas na atenção primária (48)(49) .…”
Section: Enfermagem Gerontológicaunclassified
“…For consolidating this model of health surveillance in PHC, the nurse actions are essential for performing the necessary skills for integral care and the composition of the health team (1) . Therefore, the nursing work process has five complementary and interdependent dimensions: watch, manage, research, teach, and participate politically (2) . The articulation between the managerial and care dimensions makes up nursing care management; however, with fragmented and curative actions in the context of the FHS (1) , this articulation is weakened.…”
Section: Introductionmentioning
confidence: 99%